LEITURA COLETIVA DE UM TEXTO DE LITERATURA INFANTIL NO ENSINO FUNDAMENTAL: ALGUMAS MEDIAÇÕES PENSANDO O ENSINO DAS CIÊNCIAS - Carla Giulia Corsi Moreira Giraldelli; Maria José P. M. de Almeida (Ensaio Pesquisa em Educação em Ciências, 2008)
We analyse the functioning of a text of children's literature to mediate in the teaching of nature sciences for children from nine to ten years old in a classroom of the basic teaching of a public school in the Campinas city, state of São Paulo. The collective reading of the narrative text was considered with intention to stimulate the curiosity of the students and to contribute for the construction of pertinent conceptions to the area of Sciences in pleasant way. The analysis of children speaks occured during this reading and of texts written for them after the ending of the activity, it evidenced mediation of the text, mediation child-to-child, and child-to-researcher teacher. We could notice that, beyond pleasant, the activity played a significant role as investigator of abstract systematic knowledge.